Pancamain Tourism Rides Based on Traditional Toys for Media to Introducing Pancasila Values - Zaini Alif, Mohamad; M. Shidiq; Kusdiana, Hilman; Turgarini, Dewi (PANTUN: Jurnal Ilmiah Seni Budaya, 2025)
The purpose of this community service is to realize an Independent Village by improving the ability of the community is a global and national commitment in an effort to improve the welfare of the community to achieve a better and more sustainable life in the goals of sustainable development. Increasing the diversification of tourism products in the Kampung Bolang Ranca Group, through Knowledge in the implementation of the management of traditional Pancamain game tourism rides, by 80%, Increasing the skills of the Service Training Workshop through the use of Pancamain as a medium for Pancasila value education tourism rides by 80%, Increasing marketing skills to schools through the approach of learning media rides both inside and outside schools (general) 80%. The training implementation method is carried out in three stages, namely 1) Socialization of partner needs material; 2) Training and mentoring for diversification of traditional game rides; and 3) skills training in the form of improving partner capabilities in service and the ability to become more communicative instructors. The impact of the training results can be seen through the formation of divisions in managing village tourism in the Bolang cobra group, the ability in service with the availability of rides with the availability of supporting products for tourist rides, and marketing capabilities by building social media contacts and schools in Tanjungsiang and Cisalak Subang districts.